Tutores de cães consideram a dieta caseira como adequada, mas alteram as fórmulas prescritas - Halfen, Dóris P.; Oba, Patrícia M.; Duarte, Caio N.; Santos, João Paulo F.; Vendramini, Thiago Henrique A.; Sucupira, Maria Cláudia A.; Carciofi, Aulus C. [UNESP]; Brunetto, Márcio (FapUNIFESP (SciELO), 2017)
The aim of this study was to evaluate the adhesion and perception of dog owners from the city of São Paulo, Brazil, on the employment of homemade diet for the nutritional management of their pet. The participants were 55 owners that provided homemade diet for their dog. The interviews were conducted by telephone and the questionnaire included points related with the preparation and effectiveness of diets, as well as the handling of animals. It was found that a considerable number of prescriptions (45.9%) was associated with patients with hyporexia. Among the owners who reported difficulty in the preparation (10.9%), time spent (33.3%) was the most problematic topic. When questioned in relation to changes in the prescribed formulas, 60% admitted that conducted it without recommendation. In the opinion of interviewed owners, the homemade diet did not cause changes in feces (50%) and coat (62.7%) of the animals compared to the use of a commercial food and was considered appropriate by the majority (79.0%). The homemade diets can be widely used, being especially important in dogs with diseases and/or dogs with hyporexia, since they are more easily accepted than the commercial diet; however, not all owners are able for its right use.
Dog owners consider homemade diet as adequate, but change the prescribed formulas
Keywords: Dogs; Hyporexia; Nutritional management; Unconventional diets